The Lipodystrophy Syndrome in HIV-Infected Children under Antiretroviral Therapy: A First Report from the Central Africa - Honoré Kalombayi Tshamala; Loukia Aketi; Pierre Manianga Tshibassu; Mathilde Bothale Ekila; Eric Musalu Mafuta; Patrick Kalambayi Kayembe; Michel Ntetani Aloni; Joseph Diayisu Shiku (International Journal of Pediatrics)
Background. Despite the high prevalence of the HIV/AIDS, few studies focused on the prevalence of lipodystrophy in pediatric HIV patients on antiretroviral therapy (ARV) in sub-Saharan African countries. The aim of this study was to assess the prevalence and to identify the risk factors of metabolic disorders related to ARV therapy in this population. Methods. A cross-sectional study was completed in Kinshasa, the Democratic Republic of Congo. HIV-infected children aged between six and 18 years on ARV were consecutively recruited. For each case, two control children (one non-HIV infected child and one HIV-infected antiretroviral therapy-naïve child) were also recruited. Results. 80 HIV-infected on ARV therapy children (group 1), 80 noninfected children (group 2) and 65 HIV-infected antiretroviral therapy-naïve children (group 3) were recruited. The frequency of lipoatrophy was not statistically different between group 1 (16.3%) and group 3 (21.5%). A significantly higher proportion of lipohypertrophy, hypercholesterolemia, and lactic acidosis was noted in children of group 1, compared to the controls (p<0.05). Mixed form was rarely observed in this series. The frequency of hypertriglyceridemia was not different between the 3 groups (p>0.05). Conclusion. Lipohypertrophy, hypercholesterolemia, and lactic acidosis emerge as a frequent metabolic disorders due to ARV therapy.